2021
DOI: 10.1136/gpsych-2020-100446
|View full text |Cite
|
Sign up to set email alerts
|

Online single-session interventions for Kenyan adolescents: study protocol for a comparative effectiveness randomised controlled trial

Abstract: BackgroundMental health problems are the leading cause of disability among adolescents worldwide, yet access to treatment is limited. Brief digital interventions have been shown to improve youth mental health, but little is known about which digital interventions are most effective.AimsTo evaluate the effectiveness of two digital single-session interventions (Shamiri-Digital and Digital-CBT (cognitive-behavioural therapy)) among Kenyan adolescents.MethodsWe will perform a school-based comparative effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For example, future research could collect long-term follow-up measures of participants in Shamiri digital, a single-session remote intervention which showed promising reductions in depressive symptoms over the long-term [ 69 ]. This study could also compare the long-term effects of Shamiri digital to digital cognitive behavioral therapy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, future research could collect long-term follow-up measures of participants in Shamiri digital, a single-session remote intervention which showed promising reductions in depressive symptoms over the long-term [ 69 ]. This study could also compare the long-term effects of Shamiri digital to digital cognitive behavioral therapy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies with longer follow-up periods are needed to understand how long the effects persist, which would have major implications for cost-effectiveness evaluations. Relatedly, our definitions of clinically meaningful change are only meant to describe short-term response to the intervention; future research will be needed to understand if any students experience long-term recovery from online single-session interventions (see Wasil, Osborn, Weisz, et al, 2021). Finally, results from the trial come from students from one Kenyan high school.…”
Section: Discussionmentioning
confidence: 99%
“…After preliminary evaluation of included publications, we developed a categorization for interventions, as follows: psychotherapeutic, social, lifestyle/physical health, economic, and psychopharmacological interventions. About 10% of psychotherapeutic interventions utilized a singlesession intervention approach (14/144) (Stein et al, 1997;Igreja et al, 2004;Connolly and Sakai, 2011;Cubbins et al, 2012;Eller et al, 2013;Pengpid et al, 2013;Morojele et al, 2014;Lasebikan et al, 2017;De Fouchier and Kedia, 2018;Harder et al, 2020;Osborn et al, 2020;Akena et al, 2021;Wasil et al, 2021;Venturo-Conerly et al, 2022). A total of 10 studies quantitively assessed the effect of a single session intervention on MH or SU, of which eight studies indicated a statistically significant MH or SU reduction.…”
Section: Intervention Approach Categoriesmentioning
confidence: 99%